Between Objective and Subjective Architectural Experiences: Conceptualizing Refractive Neuroarchitecture Phenomenology - Yongjun Shin (Enquiry: The ARCC Journal of Architectural Research)
This analytical essay is aimed at developing a conceptual framework to assess how people experience the built environment both objectively and subjectively through a critical literature review of neuroarchitecture, architectural phenomenology, and neurophenomenology. Whereas both modes of human experience with the built environment are inseparable in real life, they have often been evaluated as seemingly antithetical and distinct approaches. Our experiences with the environment are mediated by our brains, for instance, our brain’s neurophysiological responses to colors, shapes, or heights. Such experiences are universal. Also, our experiences are constantly refracted by our unconscious subjective and intersubjective sense-making filters in the brain. Based on the critical literature review and synthesis, this study conceptualizes a refractive neuroarchitecture phenomenology, which is defined as a study of humans’ subjective and intersubjective architectural experiences through an epistemological and methodological convergence of the first- and second-person phenomenological and third-person neuroscientific methods. This conceptualization would provide intellectual significance as it attempts to integrate both objective and subjective epistemology and methodology into architectural research. For a practical implication, it is expected to demonstrate the importance of the phenomenological aspect of architectural efficacy and ways of applying neuroscientific research for place-making, including urban renewal and historic preservation.